Transdermal drug delivery - Lee, Kun Loong. (2013)
Humans have always looked for ways to improve their health or reduce pain through ingestion and administering of drugs. Transdermal drug delivery (TDD) provides a suitable and safe solution and has several advantages over oral and hypodermic injection. In particular, it is useful when the first-pass metabolism is great due to the liver and gut wall. As well as reducing the possibility of infection or transmission of disease through injections. Currently, there are 19 different TDD systems and some of their characteristics are being reviewed in this study, such as iontophoresis, chemical modification of drug and ultrasound mediated delivery. Studies were done to determine the temporal dependency of drug penetration through porcine skin of varied intensity and the maximum molecular weight for transdermal drug delivery. Nanospheres were used to simulate drug molecules and the penetration efficiency after application of ultrasound was found to increase significantly for particles of diameter 60nm and more than 5 times for particles of diameter 840nm. The damage to the structure of the skin were imaged and studied to determine the suitable parameters for therapeutic use of ultrasound TDD. The findings in this study would lay a crucial ground work for the improvement to ultrasound mediated delivery and predicting the efficiency of sonophoresis for future clinical use.